Trump’s America 2.0: Thailand’s response under China’s shadow - Suporn, Thapiporn; Bunyavejchewin, Poowin (Frontiers in Political Science, 2025)
Once a close ally of the United States, Thailand now finds itself walking a diplomatic tightrope under the shadow of Donald Trump’s second presidency and China’s growing influence. Trump’s America First doctrine, characterized by disengagement and transactionalism, has left allies such as Bangkok questioning Washington’s reliability. Confronted with the uncertainties precipitated by the Trump administration, Prime Minister Paetongtarn Shinawatra has positioned the nation closer to Beijing, even making controversial accommodations, notably the deportation of Uyghur refugees to China. Caught between two major powers, Thailand faces a political dilemma. While China’s influence is rapidly expanding, its demands risk fostering overdependence and provoking domestic backlash. Conversely, the United States now appears distant and unpredictable. This study highlights Thailand’s efforts to maintain a delicate balance amid these strategic fluctuations, urging the United States to reclaim its role as a balancer in continental Southeast Asia, where nations such as Thailand continue to seek equilibrium of major power influence amid intense geopolitical rivalry.